Conducting a Cluster Analysis in Counseling Research: Four Easy Steps. (2nd January 2021) - Bardhoshi, Gerta; Um, Byeolbee; Erford, Bradley T.
Abstract: A cluster analysis is an exploratory research method that contributes to identifying homogeneous subgroups and examining the structure of targeted data. This article provides four steps for conducting a cluster analysis for counseling researchers and practitioners: (1) select variable(s) for clustering subgroups; (2) perform preliminary data processing; (3) determine the clustering method to use; and (4) assess the validity of clustering results. Cluster analysis benefits counseling research in various ways, including offering an in-depth understanding of counselors, clients, and relevant counseling mechanisms.